Mechanism of change towards the Circular Economy: a case study in the packaging sector under the lens of Institutional Theory - Streit, Jorge Alfredo Cerqueira; Guarnieri, Patrícia; Sousa, Pedro Henrique Rodrigues de; Camillis, Patricia Kinast de (Revista de Administração da UFSM, 2023)
Purpose – This article aims to analyze normative isomorphism as a mechanism for institutional change and its potential contribution to the institutionalization of the Circular Economy in the packaging market in Brazil. Methodology – A qualitative approach through in-depth interviews with a semi-structured script. 23 people from the First sector – government, 15 people from the Second sector – market, and 15 people from the Third sector – Non-Governmental Organizations were interviewed. The snowball sampling technique was used to select the interviewees. The content analysis was conducted with categories defined while exploring the data collected, a posteriori, with NVivo software. Findings – In Brazil, the pressure for socio-environmental product improvements is concentrated on a portion of the population. Most people focus on economic issues. In addition, Non-Governmental Organizations (NGOs) and supervisory government agencies play a crucial role in directly demanding that laws are complied with and in encouraging and instructing civil society related to the Circular Economy and sustainability. Research implications – this article contributes to filling gaps identified in the literature, such as Circular Economy studies that investigate the dynamics of stakeholders. Practical implications – the research shows that there is room for organizations that operate in the packaging market in Brazil to develop and disseminate actions related to the Circular Economy and sustainability to their consumers, which can become a competitive advantage in the sector. Originality/value – the research pointed out that the perception of those involved in this supply chain is still not unanimous regarding society's demand for a circular economy and sustainable actions.